A self-supporting nickel-iron-based heterostructure catalyst and its preparation method and application
Through the preparation of self-supported nickel-iron-based heterostructure nanosheet catalysts, the existing urea oxidation catalysts have been solved, and the efficient, stable and low-cost urea oxidation reaction performance has been achieved.
Patent Information
- Application Number
- CN202411075547.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing urea oxidation catalysts have low activity, poor stability and slow kinetics under high current density, making it difficult to meet the requirements of industrial applications.
A NixSe/NiFe-LDH heterostructure catalyst was prepared by selenization of nickel foam and selenium powder and potential deposition of nickel iron deposited solution by using a self-supported nickel-iron heterostructure catalyst.
At high current density, the catalyst exhibits excellent urea oxidation reaction performance, requires a low working potential, a small Tafel slope, and has high activity, stability and low production costs.
Smart Images

Figure CN118996504B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrogen production, and in particular relates to a self-supporting nickel-iron based heterogeneous structure catalyst and a preparation method and application thereof. Background Art
[0002] Traditional fossil energy sources such as coal, oil, and natural gas are non-renewable and have limited reserves, and the CO released after their combustion 2 、SO 2 、NO x The toxic effects of products such as hydrogen on the atmosphere, water bodies, and soil environment have promoted the development of renewable clean energy. Hydrogen energy is considered to be one of the most ideal green and clean energy sources, with the advantages of sustainability, high energy density, and environmental friendliness. The electrolysis of water to produce hydrogen by coupling renewable electricity is considered to be an effective way to produce high-purity hydrogen. It includes two important half-reactions, namely the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). Compared with HER, OER involves thermodynamic upslope reactions and sluggish proton / coupled electron transfer reaction kinetics, which seriously restricts the overall hydrogen production efficiency of water electrolysis. Recent studies have shown that the use of synergistic coupled oxidation reactions of organic small molecules with good thermodynamics (such as urea, ethanol, and hydrazine hydrate, etc.) to replace OER can significantly reduce the battery voltage required for the reaction, which is an effective strategy for efficient and energy-saving hydrogen production. Urea is one of the common pollutants in industrial and agricultural wastewater. The thermodynamic potential of urea oxidation reaction (UOR) is as low as 0.37V, which is much lower than the thermodynamic potential of OER (1.23V). If UOR is coupled with the cathode HER in the water electrolysis hydrogen production system, it is expected to achieve energy-saving production of hydrogen and purification of urea-rich wastewater at the same time. However, the current challenges are mainly that the UOR process involves six electron transfer steps and complex intermediate adsorption / desorption processes, requiring highly active electrocatalysts to increase its reaction rate. The commonly used UOR catalyst is still commercial IrO 2 or RuO 2 However, they have problems such as low reserves, high prices and poor stability, which greatly limit their widespread application. Therefore, it is urgent to develop UOR catalysts that are abundant in reserves, efficient, stable, cheap and easy to obtain.
[0003] In recent years, the research on UOR catalysts has mainly focused on a series of materials such as transition metal selenides, nitrides, phosphides, oxides and hydroxides, and optimized their catalytic activity and stability by regulating their structure and composition. For example, Cui et al. developed a highly efficient chromium-doped nickel cobalt hydrotalcite (NiCoCr-LDH / NF) catalyst by a one-step hydrothermal method. In an alkaline solution containing urea, its current density was 100 mA cm -2 The potential required for the reaction was 1.38 V vs. RHE. Qiao’s team designed and prepared an optimized sulfur-oxygen anion engineered nickel powder catalyst (Ni-SOX ), the catalyst achieved 323.4 mA cm at a potential of 1.65 V. -2 The ultra-high current density and 99.3% selectivity of nitrogen products were achieved; Lu et al. loaded Pt-modified Ni(OH) on nickel carbon nanofibers by electrospinning and electrodeposition techniques. 2 (Pt-Ni(OH) 2 @Ni-CNFs) for catalytic UOR. In alkaline solution containing urea, the catalyst only requires low potentials of 1.363 and 1.422 V vs. RHE to obtain 10 and 100 mA cm -2 Despite these important advances, the reported non-precious metal UOR electrocatalysts can only operate at current densities below 500 mA cm -2 Although it shows good activity at a current density of 2.5, it still cannot meet the requirements of industrial application. Therefore, it is very necessary to rationally prepare UOR catalysts with high activity, high stability and low cost at high current density for urea-assisted water electrolysis to produce hydrogen. Summary of the invention
[0004] The purpose of the present invention is to provide a self-supporting nickel-iron based heterostructure catalyst and a preparation method and application thereof, so as to solve the problems of low activity, poor stability and slow kinetics of urea oxidation catalysts at high current density in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] Firstly, the present invention provides a method for preparing a self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction, the preparation method comprising the following steps:
[0007] (1) Place nickel foam and selenium powder in the same container, heat a tube furnace to 200-350°C under an inert atmosphere, keep the temperature, perform selenization treatment, cool to room temperature, rinse, and obtain a self-supporting Ni x Se nanofolds;
[0008] (2) The self-supporting Ni x Se nanofolds were placed in a nickel-iron deposition solution for constant potential deposition to obtain Ni x Se / NiFe-LDH heterostructure nanosheet catalyst.
[0009] Preferably, in the step (1), the mass ratio of the nickel foam to the selenium powder is 1:2-5.
[0010] Preferably, in step (1), the inert atmosphere is an argon atmosphere, the heating rate of the tubular furnace is 2-10° C. / min, and the insulation time is 1-3 h; and the rinsing is performed by rinsing with deionized water and anhydrous ethanol respectively.
[0011] Preferably, in step (2), the nickel-iron deposition solution is formed by mixing soluble nickel salt and soluble iron salt in a concentration ratio of 1-3:1-3.
[0012] Preferably, in step (2), the nickel-iron deposition solution is composed of a soluble nickel salt and a soluble iron salt in a concentration ratio of 1:3, 1:1 or 3:1.
[0013] Preferably, in step (2), the soluble nickel salt is Ni(NO 3 ) 2 6H 2 O, the soluble iron salt is Fe(NO 3 ) 3 9H 2 O.
[0014] The voltage of the constant potential deposition is -0.8V to -2V; the time of the constant potential deposition is 5 to 60 minutes.
[0015] Preferably, the urea oxidation reaction is a urea oxidation reaction under a high current density, and the high current density is 250-500 mA cm -2 .
[0016] Preferably, the high current density is 500 mA cm -2 .
[0017] Secondly, the present invention provides a self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction under high current density, and the self-supporting nickel-iron-based heterostructure nanosheet catalyst is prepared by the above-mentioned preparation method of a self-supporting nickel-iron-based heterostructure nanosheet catalyst.
[0018] Preferably, the high current density is 250-500 mA cm -2 .
[0019] Preferably, the high current density is 500 mA cm -2 .
[0020] Secondly, the present invention provides an application of a self-supporting nickel-iron-based heterostructure nanosheet catalyst in a urea oxidation reaction under a high current density. When the self-supporting nickel-iron-based heterostructure nanosheet catalyst is used in a urea oxidation reaction under a high current density, Ni xSe / NiFe-LDH heterostructure nanosheet catalyst was used as the working electrode, saturated Hg / HgO electrode was used as the reference electrode, and carbon rod was used as the counter electrode;
[0021] The self-supporting nickel-iron-based heterostructured nanosheet catalyst is prepared by the above-mentioned method for preparing a self-supporting nickel-iron-based heterostructured nanosheet catalyst.
[0022] Preferably, when the current density is 250 mA cm -2 When, the required working potential is 1.382~1.402V;
[0023] When the current density is 500 mA cm -2 The required working potential is 1.396~1.416V.
[0024] Secondly, the present invention provides a method for urea oxidation reaction under high current density using a self-supporting nickel-iron-based heterostructure nanosheet catalyst, wherein the method comprises: in an alkaline environment containing urea, using Ni x Se / NiFe-LDH heterostructure nanosheet catalyst was used as the working electrode, saturated Hg / HgO electrode was used as the reference electrode, and carbon rod was used as the counter electrode for urea oxidation reaction.
[0025] Preferably, in the method, when the current density is 250 mA cm -2 When, the required working potential is 1.382~1.402V;
[0026] When the current density is 500 mA cm -2 When, the required working potential is 1.396~1.416V;
[0027] The self-supporting nickel-iron-based heterostructured nanosheet catalyst is prepared by the above-mentioned method for preparing a self-supporting nickel-iron-based heterostructured nanosheet catalyst.
[0028] Secondly, the present invention provides a device for urea oxidation reaction at high current density, wherein the working electrode of the device is Ni x Se / NiFe-LDH heterogeneous structure nanosheet catalyst, the reference electrode of the device is a saturated Hg / HgO electrode, and the counter electrode of the device is a carbon rod.
[0029] The Ni x The Se / NiFe-LDH heterostructured nanosheet catalyst is a self-supporting nickel-iron-based heterostructured nanosheet catalyst, and the self-supporting nickel-iron-based heterostructured nanosheet catalyst is prepared by the above-mentioned preparation method of a self-supporting nickel-iron-based heterostructured nanosheet catalyst.
[0030] The beneficial effects of the present invention are:
[0031] 1. Highly efficient catalytic performance: the self-supporting Ni x The Se / NiFe-LDH heterostructure catalyst exhibits excellent urea oxidation performance in alkaline solution containing urea. 2 The catalyst can achieve high current density at a lower potential and has a smaller Tafel slope, so it has higher catalytic activity and kinetic performance.
[0032] 2. Excellent stability: The catalyst is stable at 500mAcm 2 At an industrial-grade current density of 1.5 MW, after long-term continuous operation, no significant change in potential was observed, showing excellent electrochemical stability. This means that the catalyst has good durability and reliability in practical industrial applications.
[0033] 3. Cheap and easily available: The present invention uses abundant and inexpensive elements such as nickel, iron and selenium as raw materials to replace precious metal catalysts, which significantly reduces the production cost of the catalyst and is conducive to large-scale industrial applications.
[0034] 4. Easy to prepare and highly controllable: The present invention adopts a simple low-temperature selenization method and electrodeposition technology to prepare the catalyst. By adjusting the ratio of nickel and iron ions and the selenization temperature, the structure and composition of the catalyst are optimized, ensuring the repeatability of the preparation process and the high quality of the product.
[0035] 5. Superior structure: Through surface morphology and structural analysis, it is found that self-supporting Ni x The Se / NiFe-LDH heterostructure catalyst has a nanosheet morphology and a clear crystalline / amorphous heterointerface. This structure is conducive to promoting electron transfer, increasing the specific surface area and active sites of the catalyst, and thus improving its catalytic performance.
[0036] 6. Environmental protection and high energy efficiency: By coupling the urea oxidation reaction (UOR) with the cathode hydrogen evolution reaction (HER), energy-saving production of hydrogen is achieved, while urea-rich wastewater is effectively purified, achieving the dual effects of environmental protection and efficient energy utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 For self-supporting x Linear sweep voltammetry (LSV) and Tafel slope diagram of Se / NiFe-LDH heterostructure catalyst in alkaline environment containing urea;
[0038] Figure 2 For self-supporting xLinear sweep voltammetry (LSV) and Tafel slope plot of Se / NiFe-LDH heterostructure catalyst in alkaline environment containing human urine;
[0039] Figure 3 For self-supporting x Transmission electron microscopy (TEM) images and high-resolution transmission electron microscopy (HR-TEM) images of Se / NiFe-LDH heterostructure catalysts;
[0040] Figure 4 For self-supporting x XRD pattern of Se / NiFe-LDH heterostructure catalyst. DETAILED DESCRIPTION
[0041] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with specific embodiments and drawings.
[0042] The present invention synthesizes the self-supporting Ni x The raw materials required for Se / NiFe-LDH heterostructure urea oxidation catalyst can be purchased through commercial channels.
[0043] Example 1
[0044] This embodiment 1 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0045] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 = 0.1023 g, then weigh the mass of selenium powder and record it as m 2 =0.2046g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0046] (2) Take 0.01 mmol of Ni(NO 3 ) 2 6H 2 O and 0.03 mmol Fe(NO 3 ) 3 9H 2O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0047] In this embodiment 1, the total amount of ions in the nickel-iron deposition solution is 0.04 mmol, and the ratio of nickel-iron ions is 1:3.
[0048] Example 2
[0049] This embodiment 2 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0050] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 = 0.1026g, then weigh the mass of selenium powder and record it as m 2 =0.2052g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0051] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0052] In this embodiment 2, the total amount of ions in the nickel-iron deposition solution is 0.04 mmol, and the ratio of nickel-iron ions is 1:1.
[0053] Example 3
[0054] This embodiment 3 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0055] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 =0.1025g, then weigh the mass of selenium powder and record it as m 2 =0.205g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0056] (2) Take 0.03 mmol of Ni(NO 3 ) 2 6H 2 O and 0.01 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0057] In this embodiment 3, the total amount of ions in the nickel-iron deposition solution is 0.04 mmol, and the ratio of nickel-iron ions is 3:1.
[0058] Comparative Examples 1, 2, and 3 obtained under different nickel-iron ion ratios x The Se / NiFe-LDH heterostructure catalyst has better urea oxidation performance when the total ion content of the nickel-iron deposition solution is 0.04 mmol and the ratio of nickel-iron ions is 1:1.
[0059] Example 4
[0060] This embodiment 4 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0061] (1) Weigh a piece of 1×3cm 2The mass of the nickel foam is recorded as m1 = 0.1029 g, and then the mass of the selenium powder is weighed and recorded as m 2 =0.2058 g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 200°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0062] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0063] Example 5
[0064] This embodiment 5 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0065] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 = 0.1022g, then weigh the mass of selenium powder and record it as m 2 =0.2044 g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 250°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0066] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0067] Example 6
[0068] This embodiment 6 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0069] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 =0.1019g, then weigh the mass of selenium powder and record it as m 2 =0.2038 g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 300°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0070] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0071] Comparison of the self-supporting Ni obtained at different selenization temperatures in Examples 2, 4, 5, and 6 x The Se / NiFe-LDH heterostructure catalyst has better urea oxidation performance when the selenization temperature is 350℃.
[0072] Example 7
[0073] This embodiment 7 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0074] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 = 0.1023 g, then weigh the mass of selenium powder and record it as m 2 =0.2046g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0075] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0076] Example 8
[0077] This embodiment 8 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0078] (1) Weigh a piece of 1×3cm 2 The mass of the nickel foam is recorded as m1 = 0.1025 g, and then the mass of the selenium powder is recorded as m 2 =0.205g, m 2 =2m 1; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0079] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0080] Comparison of the self-supporting Ni obtained under different deposition potentials in Examples 2, 7, and 8 x The Se / NiFe-LDH heterostructure catalyst has better urea oxidation performance when the deposition potential is -1.2V.
[0081] Example 9
[0082] This embodiment 9 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0083] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 = 0.1027g, then weigh the mass of selenium powder and record it as m 2 =0.5135g, m 2 =5m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 5°C / min and keep it warm for 3h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0084] (2) Take 0.02 mmol of Ni(NO 3 )2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0085] Example 10
[0086] This embodiment 10 provides a self-supporting Ni x The preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0087] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 =0.1024g, then weigh the mass of selenium powder and record it as m 2 =0.3072g, m 2 =3m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 10°C / min and keep it warm for 1h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0088] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0089] Embodiment 11
[0090] This embodiment 11 provides a self-supporting Ni xThe preparation method of Se / NiFe-LDH heterostructure urea oxidation catalyst comprises the following steps:
[0091] (1) Weigh a piece of 1×3cm 2 The mass of nickel foam is denoted as m 1 =0.1025g, then weigh the mass of selenium powder and record it as m 2 =0.41g, m 2 =4m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 6°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized samples were rinsed with deionized water and anhydrous ethanol respectively, and dried with nitrogen to obtain a self-supporting Ni x Se;
[0092] (2) Take 0.02 mmol of Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added to the electrolytic cell as nickel-iron deposition solution, and the self-supporting Ni x Se was used as the working electrode, saturated calomel as the reference electrode, and platinum mesh as the counter electrode. The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst.
[0093] Comparative Example 1
[0094] This comparative example 1 provides a method for preparing a self-supporting NiFe-LDH urea oxidation catalyst, comprising the following steps:
[0095] Take 0.02mmol Ni(NO 3 ) 2 6H 2 O and 0.02 mmol Fe(NO 3 ) 3 9H 2 O was added into the electrolytic cell as nickel-iron deposition solution, nickel foam was used as working electrode, saturated calomel was used as reference electrode and platinum mesh was used as counter electrode, and deposition was carried out at a constant potential of -1.2 V for 10 min to obtain a self-supported NiFe-LDH catalyst.
[0096] Comparative Example 2
[0097] This comparative example 2 provides a self-supporting Ni xThe preparation method of Se urea oxidation electrocatalyst comprises the following steps:
[0098] Weigh a piece of 1×3cm 2 The mass of the nickel foam is recorded as m1 = 0.1021 g, and then the mass of the selenium powder is weighed and recorded as m 2 =0.2041g, m 2 =2m 1 ; Place the two at the two ends of the same porcelain boat, then put the porcelain boat into the middle of the tube furnace, so that the selenium powder is located upstream of the tube furnace. In a high-purity argon atmosphere, heat the tube furnace to 350°C at a heating rate of 2°C / min and keep it warm for 2h to perform selenization treatment. After cooling to room temperature, the selenized sample was rinsed with deionized water and anhydrous ethanol respectively, and then dried with nitrogen to obtain a self-supporting Ni x Se.
[0099] Experimental example
[0100] Take the self-supporting Ni prepared in Example 2 x Se / NiFe-LDH heterostructure catalyst was used to test its catalytic performance in urea oxidation / oxygen evolution reaction. x Se / NiFe-LDH heterostructure catalyst was used as working electrode, saturated Hg / HgO electrode was used as reference electrode, carbon rod was used as counter electrode, alkaline solution containing / not containing urea was used as electrolyte, and the performance test of electrocatalytic urea oxidation / oxygen evolution reaction was carried out using Shanghai Chenhua CHI-604EE electrochemical workstation. x Se catalyst and commercial RuO 2 The catalyst was tested for urea oxidation performance under the same conditions. Figure 1 As shown:
[0101] Reference Figure 1 a is the self-supporting Ni obtained in Example 2 x Performance test of Se / NiFe-LDH heterostructure catalyst for electrocatalytic urea oxidation / oxygen evolution reaction in alkaline solution containing / not containing urea: Performance test of electrocatalytic urea oxidation reaction was carried out in 1.0M KOH solution containing 0.5M urea; Performance test of electrocatalytic oxygen evolution reaction was carried out in 1.0M KOH solution.
[0102] in:
[0103] For electrocatalytic oxygen evolution reaction, self-supported Ni x Se / NiFe-LDH heterostructure catalyst achieves 500 mA cm -2When the industrial current density is 1.512V, the potential required is 1.512V; for the electrocatalytic urea oxidation reaction, it obtains 500mAcm -2 At an industrial-grade current density of 1.396 V, the required applied potential is only 1.396 V, indicating that the urea oxidation reaction occurs preferentially on the self-supporting Ni x Se / NiFe-LDH heterostructure catalyst. In addition, self-supporting Ni x The constant current stability of Se / NiFe-LDH heterostructure catalyst in 1.0 M KOH solution containing 0.5 M urea was 500 mA cm after continuous operation for 200 h. -2 No obvious change was observed in the potential applied at the industrial-grade current density, indicating that the catalyst has excellent stability at the industrial-grade current density.
[0104] Reference Figure 1 b~d are the self-supporting Ni obtained in Example 2 x Se / NiFe-LDH heterostructure catalyst, the self-supporting NiFe-LDH catalyst obtained in Comparative Example 1, and the self-supporting Ni x Se catalyst and commercial RuO 2 Performance test of the catalyst for electrocatalytic urea oxidation reaction in an alkaline solution containing urea: The performance test of the electrocatalytic urea oxidation reaction was carried out in a 1.0 M KOH solution containing 0.5 M urea.
[0105] in:
[0106] In a 1.0 M KOH solution containing 0.5 M urea, the self-supporting Ni x Se / NiFe-LDH heterostructure catalyst achieves 500 mA cm -2 At the industrial current density, the required applied potential is 1.396 V, and the corresponding Tafel slope is 32.3 mVdec -1 ;
[0107] In 1.0 M KOH solution containing 0.5 M urea, the self-supported NiFe-LDH catalyst obtained 500 mA cm -2 At the industrial current density, the required applied potential is 1.480 V, and the corresponding Tafel slope is 51.1 mV dec. -1 .
[0108] In a 1.0 M KOH solution containing 0.5 M urea, the self-supporting Ni x Se catalyst achieved 500 mA cm -2 At an industrial current density of 1.447 V, the required applied potential is 1.447 V, and the corresponding Tafel slope is 38.2 mV dec.-1 .
[0109] Commercial RuO was dissolved in 1.0 M KOH solution containing 0.5 M urea. 2 The catalyst obtained 500mAcm -2 When the industrial current density is 1.501V, the required applied potential is 1.501V, and the corresponding Tafel slope is 65.4mV dec-1.
[0110] Reference Figure 2 a is the self-supporting Ni obtained in Example 2 x Actual picture of the performance test device of Se / NiFe-LDH heterostructure catalyst for electrocatalytic urea oxidation reaction in an alkaline solution containing human urine.
[0111] Reference Figure 2 b~d are the self-supporting Ni obtained in Example 2 x Se / NiFe-LDH heterostructure catalyst, the self-supporting NiFe-LDH catalyst obtained in Comparative Example 1, and the self-supporting Ni x Se catalyst and commercial RuO 2 The performance of the catalyst was tested for the electrocatalytic urea oxidation reaction in an alkaline solution containing human urine.
[0112] in:
[0113] In 1.0 M KOH solution containing human urine, the self-supporting Ni x Se / NiFe-LDH heterostructure catalyst achieves 500 mA cm -2 At the industrial current density, the required applied potential is 1.401 V, and the corresponding Tafel slope is 36.5 mVdec -1 In addition, free-standing Ni x Se / NiFe-LDH heterostructure catalyst at 500 mA cm -2 The constant current stability under industrial-grade current density, after 200 hours of continuous operation, no obvious change in the applied potential was observed. It showed excellent stability in an alkaline environment containing human urine, and has broad prospects for industrial applications.
[0114] In 1.0 M KOH solution containing human urine, the self-supported NiFe-LDH catalyst achieved 500 mA cm -2 At the industrial current density, the required applied potential is 1.488 V, and the corresponding Tafel slope is 41.3 mV dec. -1 .
[0115] In 1.0 M KOH solution containing human urine, the self-supporting Ni xSe catalyst obtained 500mAcm -2 When the industrial current density is 1.450V, the required applied potential is 1.450V, and the corresponding Tafel slope is 39.1mV dec-1.
[0116] Commercial RuO 2 The catalyst obtained 500mAcm -2 At an industrial current density of 1.497 V, the required applied potential is 1.497 V, and the corresponding Tafel slope is 77.7 mV dec. -1 .
[0117] pass Figure 1 b~d, Figure 2 b~d test results show that in alkaline solution containing urea or human urine, the self-supporting Ni x The potential and Tafel slope of Se / NiFe-LDH heterostructure catalyst are smaller than those of self-supported NiFe-LDH catalyst and self-supported Ni x Se catalyst and commercial RuO 2 The electrocatalyst showed the highest activity and kinetic performance and was most suitable as a urea oxidation catalyst.
[0118] In addition, the self-supporting Ni x The surface morphology and structure of Se / NiFe-LDH heterostructure catalyst were analyzed. Figure 3 The self-supporting Ni x TEM and HR-TEM images of Se / NiFe-LDH heterostructure catalyst. Figure 3 In a, a self-supporting Ni x The surface morphology of Se / NiFe-LDH heterostructure catalyst is nanosheets. Figure 3 The HR-TEM image of b reveals the existence of a clear crystalline / amorphous heterointerface in the catalyst. Figure 4 The self-supporting Ni x Se / NiFe-LDH heterostructure catalyst, NiFe-LDH catalyst obtained in Comparative Example 1, and self-supporting Ni x The XRD spectrum of the Se catalyst shows that the self-supporting Ni x Se catalyst is NiSe 2 and Ni 3 Se 4 Two crystal phases, and self-supporting Ni x The XRD patterns of Se / NiFe-LDH heterostructure catalysts were similar to those of free-standing Ni xSe catalyst is almost completely the same, from which it is inferred that NiFe-LDH obtained by constant potential deposition may exist in an amorphous form. Subsequently, NiFe-LDH was further analyzed by XRD, and only three diffraction peaks of nickel foam were observed in the XRD spectrum of NiFe-LDH, which confirmed that NiFe-LDH obtained by constant potential deposition exists in an amorphous form.
[0119] Of course, the above preferred embodiments are only used to express the technical implementation scheme of the present invention. Although the description is relatively specific and detailed, those skilled in the art should understand that the above description is not a limitation of the present invention. Without departing from the essential scope of the present invention, several changes, substitutions and improvements can be made in form and details, which should also belong to the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the attached claims.
Claims
1. A method for preparing a self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction, characterized in that: The self-supporting nickel-iron-based heterostructure nanosheet catalyst is Ni x Se / NiFe-LDH heterostructure nanosheet catalyst, the preparation method comprises the following steps: (1) Place nickel foam and selenium powder in the same container, heat a tube furnace to 200-350°C under an inert atmosphere, keep the temperature, perform selenization treatment, cool to room temperature, rinse, and obtain a self-supporting Ni x Se nanofolds; (2) The self-supporting Ni x Se nanofolds were placed in a nickel-iron deposition solution for constant potential deposition to obtain Ni x Se / NiFe-LDH heterostructure nanosheet catalyst.
2. The method for preparing a self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction according to claim 1, characterized in that: In the step (1), the mass ratio of the nickel foam to the selenium powder is 1:2-5.
3. The method for preparing a self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction according to claim 2, characterized in that: In the step (1), the inert atmosphere is an argon atmosphere, the heating rate of the tubular furnace is 2-10°C / min, and the insulation time is 1-3h; and the rinsing is performed by rinsing with deionized water and anhydrous ethanol respectively.
4. The method for preparing a self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction according to claim 3, characterized in that: In the step (2), the nickel-iron deposition solution is prepared by mixing soluble nickel salt and soluble iron salt in a concentration ratio of 1-3:1-3.
5. The method for preparing a self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction according to claim 4, characterized in that: In the step (2), the soluble nickel salt is Ni(NO3)2·6H2O, and the soluble iron salt is Fe(NO3)3·9H2O; The voltage of the constant potential deposition is -0.8V~-2V; The constant potential deposition time is 5 to 60 minutes.
6. A self-supporting nickel-iron-based heterostructure nanosheet catalyst for urea oxidation reaction at high current density, characterized in that: The self-supporting nickel-iron-based heterostructure nanosheet catalyst is prepared by the preparation method described in claim 1.
7. Application of a self-supporting nickel-iron-based heterostructure nanosheet catalyst in urea oxidation reaction at high current density, characterized in that: The self-supporting nickel-iron-based heterostructure nanosheet catalyst is Ni x Se / NiFe-LDH heterostructure nanosheet catalyst; When the self-supporting nickel-iron-based heterostructure nanosheet catalyst is used for urea oxidation reaction at high current density, Ni x Se / NiFe-LDH heterostructure nanosheet catalyst was used as the working electrode, saturated Hg / HgO electrode was used as the reference electrode, and carbon rod was used as the counter electrode; The self-supporting nickel-iron-based heterostructure nanosheet catalyst is prepared by the preparation method described in claim 1.
8. The use of a self-supporting nickel-iron-based heterostructure nanosheet catalyst in urea oxidation reaction under high current density according to claim 7, characterized in that: When the current density is 250 mA cm -2 When , the required working potential is 1.382~1.402 V; When the current density is 500 mA cm -2 The required working potential is 1.396~1.416 V.
Citation Information
Patent Citations
Ferronickel-based nanosheet array based on carbon cloth growth as well as preparation and application thereof
CN109811365A
Self-supporting Ni2P-NiFeBP / S heterojunction catalyst, preparation method and application thereof
CN118308753A